2008
DOI: 10.3844/ajbbsp.2008.255.264
|View full text |Cite
|
Sign up to set email alerts
|

Novel Metal Accumulator and Protease Secretor Microbes from East Calcutta Wetland

Abstract: Nine bacterial isolates were screened from different sites of East Calcutta Wetland, an ecosystem located at the eastern fringes of Calcutta. Other than being a biodiversity rich area, the important feature of this system is that it is a natural sewage treatment plant for the city of Calcutta. In addition to daily sewage including solid and soluble wastes, a considerable load of toxic metals are released into the water bodies from industries, tanneries, agriculture, household as well as health sectors. Screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…As a result, they produce and accumulate large amounts of sulfide which transfer across the membrane into the culture medium and could be used as sulfur source in the formation of PbS nanoparticles. This property of metal particle generation enables the bacteria to work as a living factory and as an inexpensive system to produce metal nanoparticles which have a strong application in the field of material science (Chowdhury et al, 2008). The mechanism of PbS synthesis by B. anthracis PS2010 is suggested to be a precipitation of Pb by DMDS off gas produced by the cells from methionine amino acid in the form of PbS nanoparticles (Macaskie et al, 2007).…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, they produce and accumulate large amounts of sulfide which transfer across the membrane into the culture medium and could be used as sulfur source in the formation of PbS nanoparticles. This property of metal particle generation enables the bacteria to work as a living factory and as an inexpensive system to produce metal nanoparticles which have a strong application in the field of material science (Chowdhury et al, 2008). The mechanism of PbS synthesis by B. anthracis PS2010 is suggested to be a precipitation of Pb by DMDS off gas produced by the cells from methionine amino acid in the form of PbS nanoparticles (Macaskie et al, 2007).…”
Section: +mentioning
confidence: 99%
“…Aqueous solutions of the metal salts: CdCl 2 -2H 2 O, CuSO 4 -5H 2 O, CoCl 2, ZnSO 4 -7H 2 O and Pb(NO 3 ) 2 were prepared in de-ionized water and 0.1 mM/L were added to the nutrient agar medium. Media were sterilized, dispensed in Petri plates and then inoculated with bacteria; the plates were incubated at 35°C for 24 h. The tolerance was checked on the basis of growth observed within 24 h of cultivation according to Chowdhury et al (2008). The grown colonies were used for detection of minimal inhibitory concentrations (MICs) for each metal.…”
Section: Isolation and Selection Of Metals Resistance Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in isolation of oil degrading, extracellular protease producing as well as metal accumulating microbes (Adarsh et al, 2007;Chowdhury et al, 2008). The variation in microbial population at different sites of EKW through culture independent analysis reveals the underlying bio remedial activity of this area.…”
Section: Microbial Diversity and Commercial Potentialmentioning
confidence: 99%
“…Advances in information technology based data retrieval system allowed prediction of the putative functions of the different groups of microbes indicating the possible presence of metal accumulating, oil degrading, antimicrobial compound producing as well as enzyme producing bacteria which can be exploited for commercial purposes . The removal of metals from waste water during its journey through the wetland (Chattopadhyay et al, 2002) and the presence of metal accumulating microbes from EKW have been reported in a variety of studies (Adarsh et al, 2007;Chowdhury et al, 2008).…”
Section: Microbial Diversity and Commercial Potentialmentioning
confidence: 99%